Glaciers in the Anthropocene: A Biocultural View. Issue 3 (1st December 2022) - Gaudio, Daniel; Gobbi, Mauro
Abstract: Disappearing glaciers are one of the most evident signals of climate change of the current period in Earth's history, the Anthropocene. In this article, we discuss the side effects of the glacier melt from a biocultural standpoint, moving from the Southern European Alps to a global context. Specifically, we highlight what we are losing from a cultural and naturalistic perspective but also, paradoxically, what we could "gain" if we were able to understand more deeply, and with an interdisciplinary approach, glacial dynamics and their role for human society. Glaciers can teach us several stories, but we are quickly approaching the last chance to listen to them.